In memory of Vladimir Ivanovich Strakhov: Devoted to the 90th anniversary of his birth - Anna A. Golovanova (Saratov State University, 2023)
The article is dedicated to the 90th birthday of an outstanding scientist, a wonderful and bright man Vladimir Ivanovich Strakhov (1932-2021). His professional life was inextricably linked with Saratov State Pedagogical Institute named after K. Fedin and the SSU named after N. G. Chernyshevsky. Scientific interests of V. I. Strakhov lay in the field of psychology of attention, pedagogical psychology, psychology of sports, literary, musical and other types of creativity. He was a faithful guardian, successor, and exponent of the traditions of his father, who was a famous Russian scientist, the founder of the Saratov Psychological School Ivan Vladimirovich Strakhov.